Hyperresistinemia in Obese Female Dogs With Mammary Carcinoma in Benign-Mixed Tumors and Its Correlation With Tumor Aggressiveness and Survival - Nicchio, Bianca Oliveira; Barrouin-Melo, Stella Maria; Machado, Marilia Carneiro; Vieira-Filho, Carlos Humberto; Santos, Ferlando Lima; Martins-Filho, Emanoel Ferreira; Barbosa, Vivian Fernanda; Barral, Thiago Doria; Portela, Ricardo Wagner; Damasceno, Karine Araújo; Estrela-Lima, Alessandra (Frontiers in Veterinary Science, 2020)
Resistin is associated with metabolic, inflammatory, and neoplastic disorders, and is also considered a prognostic marker in human oncology. Canine mammary tumors have epidemiological, clinical, biological, and genetic characteristics similar to those of women and are proposed as a comparative study model. Here, we evaluate the serum levels of resistin in female dogs with or without mammary carcinoma in mixed tumors (CBMT) and its correlation with the proliferative potential of the tumor, obesity, and survival. Eighty dogs grouped according to the presence (50) or absence (30) of CBMT, reproductive status and body condition were assessed for weight, fat percentage and canine body mass index. The characteristic of the proliferative potential of the tumor (Ki-67) was evaluated. Ki-67 levels (p=0.024), staging (p=0.004) and grade (p=0.016) influenced the survival of the female dogs. Through a multifactorial analysis, it could be seen that the parameters proliferation index (Ki-67) (p=0.044) and staging (p=0.036) influenced the survival of the animals. Neutered and overweight dogs from the control and CBMT groups showed hyperresistinemia. Ki-67 expression and resistin levels in dogs with CBMT were higher in overweight dogs than in dogs with normal weight (p=0.0001). The survival rate of dogs with CBMT, obese and with high levels of resistin (8400 µg L-1) was lower when compared to those with lower levels of resistin. These results showed an important relationship between hyperresistinemia, tumor proliferative potential and excessive body fat, suggesting that resistin levels may act as an interesting prognostic marker in patients with CBMT.